Pengembangan Sistem Informasi Pelaporan Transaksi Penjualan Dengan Multilokasi dan Multi Harga Produk Pada Konter - Riki Afriansyah; Yuliyanto (Manutech : Jurnal Teknologi Manufaktur, 2020)
Abstract Counter sales transaction reports such as credit transactions, electricity tokens, data package vouchers, and others are very important for the counter owner to make a decision on adding stock of Non PPOB products or deposit balances for PPOB transactions. The problem is when the counter owner still uses conventional sales transaction records and has more than one location with different product selling prices based on sales locations. Therefore we need an information system to facilitate the management of sales transaction reports even though there are many branches with distant multilocation and multiproduct prices that differ from each sales location. To develop information systems using the waterfall method which consists of system requirements analysis, system design, implementation, testing, and evaluation. The system design uses Unified Modeling Language (UML) which consists of use case diagrams, activity diagrams, sequence diagrams and class diagrams because the system built is object oriented. The results of testing the system using the black box method obtained from the twelve functions that were tested 100% successfully run as expected. The results of the evaluation of the processing time of the daily transaction report in the conventional manner at three locations require 1 hour 30 minutes while using the information system only requires less than 1 minute.